The Value оf The Tax Audit In The Republic оf Kazakhstan аnd The Methodology оf Its Conduct - Джаксыбекова, А.; Каипова, Г. (Journal of Economic Research & Business Administration, 2019)
The purpose of the study is devoted to the study of tax audit in the Republic of Kazakhstan. The main reasons for the relevance and necessity of the existence of this type of audit services are identified. The role of the tax accounting system operating in the Republic is indicated. A description of the tax audit as a whole is given, and the consequences of a properly conducted audit are found. The impact of legislation on the quality of the audit was also noted. Originality / value – criteria are formulated that must be taken into account when drawing up a plan for the upcoming audit, due to the possibility of a risk of not detecting intentional deviations or inadvertent errors. The article also talks about the desirable model of relations between the state, the auditor, and the tax agent. Certain problems have been identified that arise during the audit of taxation in commercial companies. Findings – identified the need to improve the methodology of the audit and made recommendations to achieve this goal.